Parï¿½metros sanguï¿½neos de frangos de corte alimentados com dietas suplementadas com sementes secas de Piper cubeba como aditivo fitogï¿½nico - Domingues, Rodolfo M. [UNESP]; Laurentiz, Antonio C.; Melo, Alan P.F.; Mello, ï¿½rica S. [UNESP]; Filardi, Rosemeire S.; Sobrane Filho, Sergio T.; Silva, Marcio L.A.; Laurentiz, Rosangela S. [UNESP] (FapUNIFESP (SciELO), 2016)
Two experiments were conducted to evaluate the use of dried seeds of Piper cubeba in the diets of 1 to 21-day-old broilers and its effect on biochemical blood profile and biometry of the organs. In each experiment, 240 one-day-old male broiler chicks Cobb were distributed in a completely randomized design with five treatments and four replicates of 12 birds per experimental plot. The first experiment evaluated the use of Piper cubeba in considered highly digestible diets based on corn and soybean meal, and the second evaluated the use of pepper in low digestibility diets, which were obtained with the inclusion of meat and bone meal. Regarding the blood chemistry profile data of the experiment I, with the exception of gamma glutamyl transferase, all other serum levels were within recommended limits for poultry, and only triglyceride levels differed between treatments (P >0.05). In the second experiment there was significant difference in albumin levels, cholesterol and uric acid, but this was not the result of metabolic disorders, because except for the gama glutamyl transferase levels, all variables were within recommended levels. In both experiments, there were no differences (P< 0.05) for the biometry of organs. The conditions under which the experiments were performed at inclusion of Piper cubeba seeds in feed for broilers has not provided any toxicity to poultry.
Blood parameters of broiler chickens fed diets supplemented with dried seeds of Piper cubeba as an phytogenic additive